Participatory Approach to Watershed Management in India - Kaushik, P. K.; Pandey, B. K.; Tripathi, Y. C. (Indian Forester, 2007)
Watershed development programmes are aimed to mitigate the adverse effect of drought on crops and livestock, controlling desertification, encouraging restoration of ecological balance and promoting economic development of village community. Being a people oriented programme, it requires people's participation at various levels. Participatory approach is indeed a dynamic group process in which all members of a group contribute to the attainment of common objectives, share benefits accruing from group activities, exchange information and experience of common interest, and follow the rules, regulations and other decisions made by the group. Need for people's participation is articulated in terms of efficiency and/or costeffectiveness, equity in distribution of benefits, sustainability and empowerment of the people. In recent years watershed management has become the focal point of agricultural and rural development in rainfed areas of India and there has been increasing decentralization of responsibilities for management of natural resources to the community level. Role of people's participation and community organization in management of watersheds are discussed in this paper.